The Leadership Style and Approach: The Leadership Style and Approach - Teuku Syawal (Program Studi Manajemen Pendidikan, 2020)
Abstract: This article is an article about the style and approach of leadership in an organization. The leadership styles and approaches discussed are about leaders as The Strongman, Super Leadership, The Transactor, The Visionary Leader and Spiritual Leadership. Writing this journal is writing by using literature study. The results of this journal reveal that (1) A leader as a person who has the power to influence subordinates, (2) a leader must be able to develop the organization by developing the ability of self and subordinates and carry out their duties and responsibilities properly, (3) leaders who can design and regulate the mechanism of work and work with subordinates according to their abilities and expertise, (4) visionary leaders must have intelligent and critical characters to face various situations and generate new ideas, and (5) leaders must have values, attitudes and behaviors that can motivate yourself and subordinates.